Predicting Trustworthiness Across Cultures: An Experiment - Zylbersztejn, Adam; Babutsidze, Zakaria; Hanaki, Nobuyuki (Frontiers in Psychology, 2021)
We contribute to the ongoing debate in the psychological literature on the role of ``thin slices'' of observable information in predicting others' social behavior, and its generalizability to cross-cultural interactions. We experimentally assess the degree to which subjects, drawn from culturally different populations (France and Japan), are able to predict strangers' trustworthiness based on a set of visual stimuli (mugshot pictures, neutral videos, loaded videos, all recorded in an additional French sample) under varying cultural distance to the target agent in the recording. Our main finding is that cultural distance is not detrimental for predicting trustworthiness in strangers, but that it may affect the perception of different components of communication in social interactions.